Examples of Ricci Solitons (Journal of Mathematical Study, 2025)
In this survey paper, we discuss various examples of Ricci solitons and theirconstructions. Some open questions related to the rigidity and classification of Riccisolitons will be also discussed through those examples.
Keywords: Ricci flow; Ricci soliton; ancient solution; singularity model.